Comparative in vitro activity of Delafloxacin and other antimicrobials against isolates from patients with acute bacterial skin, skin-structure infection and osteomyelitis - Ághata Cardoso da Silva Ribeiro; Fernanda Fernandes Santos; Tiago Barcelos Valiatti; Michael Henrique Lenzi; Ingrid Nayara Marcelino Santos; Raíssa Fidelis Baêta Neves; Ikechukwu Benjamin Moses; Jaqueline Pilon de Meneses; Renata Gebara de Grande Di Sessa; Mauro José Salles; Ana Cristina Gales (Brazilian Journal of Infectious Diseases)
The aim of this study was to compare the in vitro activity of delafloxacin with other fluoroquinolones against bacterial pathogens recovered from inpatients with osteomyelitis, Acute Bacterial Skin and Skin-Structure Infections (ABSSSI). In total, 100 bacterial isolates (58 % Gram-negative and 42 % Gram-positive) recovered from inpatients between January and April 2021, were reidentified at species level by MALDI-TOF MS. Antimicrobial susceptibility testing was conducted using the broth microdilution method and the detection of biofilm formation was assessed through the microtiter plate assay. The screening for mecA was carried out by PCR, while mutations in the Quinolone Resistance Determining Regions (QRDR), specifically gyrA and parC, were analyzed using PCR followed by Sanger sequencing. Results showed that delafloxacin exhibited greater in vitro potency (at least 64-times) than the other tested fluoroquinolones (levofloxacin and ciprofloxacin) when evaluating Staphylococcus aureus (MIC50 ≤0.008 mg/L) and coagulase-negative Staphylococcus (MIC50 0.06 mg/L). Furthermore, delafloxacin (MIC50 0.25 mg/L) was at least 4 times more potent than other tested fluoroquinolones (MIC50 1 mg/L) against P. aeruginosa. No difference in delafloxacin activity (MIC50 0.03 mg/L) was observed against Enterobacter cloacae when compared with ciprofloxacin (MIC50 0.03 mg/L). Despite presenting low activity against K. pneumoniae isolates (22.2 %), delafloxacin exhibited twice the activity compared to both levofloxacin and ciprofloxacin. Delafloxacin also exhibited a strong activity (71.4 %‒85.7 %.) against biofilm producing bacterial pathogens tested in this study. Interestingly, 82.14 % of the staphylococci tested in this study harbored mecA gene. In addition, the gyrA and parC genes in fluoroquinolone-resistant Gram-negative isolates displayed different mutations (substitutions and deletions). Herein, we showed that delafloxacin was the most active fluoroquinolone against staphylococci (including MRSA) and P. aeruginosa when compared to other fluoroquinolones such as ciprofloxacin and levofloxacin.